RESULTS OF SURGICAL TREATMENT OF CRANIOORBITAL BRAIN TUMOR (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The problem of surgical treatment of neoplasms located in the cranio-orbital region and orbital cavity has long attracted the attention of researchers. The complexity of removing such neoplasms consists of both the dense arrangement of neurovascular and muscular structures in a small volume of the orbit, and the possible spread of the tumor into the adjacent cavities of the paranasal sinuses and the cranial cavity. A possible solution is to develop adequate surgical approaches. Historically, the development of surgery for neoplasms of the cranio-orbital region and orbit occurred in accordance with 2 approaches: extracranial and intracranial. In 1874, H. Knapp [Cited by 4], using the conjunctival superior orbitotomy developed by him, removed a retrobulbar tumor, preserving the eyeball, and in 1889 R. U. Kronlein proposed resecting the lateral wall of the orbit to remove a tumor of the muscular funnel [Cited by 4]. In 1922, the American neurosurgeon WEDandy was the first to remove a tumor from the orbit using a transcranial intradural approach, performing an osteoplastic trepanation of its upper wall from a subfrontal approach [6,7]. In Russia, the first work devoted to transcranial surgery of orbital tumors was an article by A.G. Zhagrin [2], which proposed improving the classic WEDandy approach by using an extradural approach to the orbital roof. In subsequent years, modifications to the transcranial approach concerned only the nature of the trepanation window.